Characteristics of participants and decliners from a randomized controlled trial on physical activity in patients with rheumatoid arthritis: a retrospective register-based cross-sectional study. (2nd January 2023) - Thomsen, T; Esbensen, BA; Hetland, ML; Aadahl, M
Abstract : Objective: A randomized controlled trial [Joint Resources – Sedentary Behaviour (JR-SB) intervention] aimed to reduce sedentary behaviour and increase light-intensity physical activity in patients with rheumatoid arthritis (RA) through motivational counselling and text messages. Since a large proportion of invited patients declined to participate, this study aims to compare sociodemographic, clinical, and lifestyle factors between included patients and patients declining to participate (non-participants) in the JR-SB study and to investigate which characteristics were associated with participation. Method: A register-based cross-sectional study was conducted. All patients invited to participate in the JR-SB study were identified in the DANBIO registry, from which patients' clinical and lifestyle data were also retrieved. Data on sociodemography and comorbidity were extracted from national registers. Differences between participants and non-participants were determined by an independent t-test or a chi-squared test. Logistic regression analyses adjusted for various confounders tested the association of patient characteristics with the likelihood of participation in the JR-SB study. Results: A total of 467 (58%) declined participation in the JR-SB study. Non-participants were older and less educated, more were smokers, fewer performed regular physical activity, and more had comorbidity compared to participants. Regression analyses showed that a higher educational level and absence of comorbidity in particular were associated with participation in the JR-SB study. Conclusion: Patients with RA who are less educated and with certain types of comorbidity are less motivated to participate in a physical activity intervention. The findings may inform the recruitment process and implementation of physical activity interventions in rheumatology clinical practice.